Backwardness and bondage: agrarian relations in a South Bihar district - Mundle, Sudipto (New Delhi, 1979)
The plan of chapters is as follows. Chapter 1 briefly reviews the history of Palamau's economic development and presents a statistical account of the district. A general description of the selected villages is also included here. Chapter 2 presents the data on distribution of land and other assets in the selected villages. While the household is the ultimate economic unit here as well as in subsequent chapters, differentiation is represented between as well as within individual classes. The classes themselves are identified with reference to the labour capital relationship. The same scheme of classes is used in Chapter 3 which summarises data on the economic functioning of different classes, i.e., production, labour and consumption. Consolidated household budgets of income and expenditure are also presented here which show up surplus and deficit categories of households. Against the background of these earlier chapters the phenomenon of bondage itself is analysed in Chapters 4 and 5. Chapter 4 presents the basic analytical framework and also gives a historical account of the origin of debt-bondage in Palamau. The empirical evidence on different aspects of the contemporary structure of bondage is put together in Chapter 5. The last section of this chapter (3.3) on 'Motivations for Holding Bonded Labour' is especially important for it contains the core of our own analysis of the phenomenon of bondage. The last chapter attempts to formulate a framework of policy based on the analysis which precedes it and suggests a specific package of interventions which would atleast minimise the incidence of bonded labour even if the system cannot be altogether eliminated in the short run.
Keywords: Land records